Labor Management in Company Operations - Hasyim Hasyim; Muhammad Bakri (Pascasarjana STIE Amkop Makassar, 2023)
This study explores the critical factors influencing labor management in company operations, focusing on technological integration, workplace flexibility, diversity and inclusion (D&I), performance-based incentives, and Strategic Human Resource Management (SHRM). A mixed-methods approach was employed, combining quantitative surveys with 200 mid-level and senior managers and qualitative interviews with 20 participants across various industries. The quantitative data provided statistical insights, while the qualitative data offered a deeper contextual understanding. The study identified that technological integration enhances operational efficiency and employee engagement but requires continuous upskilling and robust cybersecurity measures. Workplace flexibility improves productivity and job satisfaction but challenges maintaining team cohesion. D&I drives innovation but faces implementation barriers such as insufficient leadership commitment. Performance-based incentives motivate employees but can lead to stress and burnout if not balanced with intrinsic rewards. Effective SHRM aligns HR practices with organizational goals but requires overcoming structural and cultural barriers. These findings align with existing theories and highlight both the benefits and challenges of contemporary labor management practices. The study provides valuable insights for organizations seeking to enhance labor management practices. Practical recommendations include investing in employee training, adopting new management strategies for flexible work environments, committing to D&I initiatives, balancing extrinsic and intrinsic rewards, and viewing HR as a strategic partner. Addressing these areas can lead to improved organizational performance and employee satisfaction.